Suppression of invasive lake trout in an isolated backcountry lake in Glacier National Park. (February 2017) - Fredenberg, C. R.; Muhlfeld, C. C.; Guy, C. S.; D'Angelo, V. S.; Downs, C. C.; Syslo, J. M.
Abstract: Fisheries managers have implemented suppression programmes to control non‐native lake trout, Salvelinus namaycush (Walbaum), in several lakes throughout the western United States. This study determined the feasibility of experimentally suppressing lake trout using gillnets in an isolated backcountry lake in Glacier National Park, Montana, USA, for the conservation of threatened bull trout, Salvelinus confluentus (Suckley). The demographics of the lake trout population during suppression (2009–2013) were described, and those data were used to assess the effects of suppression scenarios on population growth rate ( λ ) using an age‐structured population model. Model simulations indicated that the population was growing exponentially ( λ = 1.23, 95% CI: 1.16–1.28) prior to suppression. However, suppression resulted in declining λ (0.61–0.79) for lake trout, which was concomitant with stable bull trout adult abundances. Continued suppression at or above observed exploitation levels is needed to ensure continued population declines.